2018
DOI: 10.21608/ejbbe.2018.3208.1016
|View full text |Cite
|
Sign up to set email alerts
|

The Dielectric Study of Calcium Hydroxylapatite Doped by Magnesium Ions

Abstract: H YDROXYAPATITE is considered as one of the most effective biomaterials with general formula Ca 10 [ PO 4 [ 6 [0H , 2 [many substances have been used for doping hydroxypatite like F, Mg, CO 3 ,Zn, Bi and Na ,to improve the properties of the HA crystal. In this paper, we discuss the influence of magnesium ions on the electrical properties of the HA crystal. Pure HA (S1) and Mg loaded hydroxy apatite (S2 ,S3 and S4) of different magnesium concentrations have been prepared by wet precipitation method .The dielect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Kanasan and his group observed that the increase in Mg content in HA P elevates the microhardness [11]. Salam and his group noticed that the increase in Mg content in HA P increases the electrical conduction and hence bioactivity of HA P increases [12]. Even though some of the researchers have studied the Zinc and Magnesium doped HA P they used a bulk amount of dopant.…”
Section: Introductionmentioning
confidence: 99%
“…Kanasan and his group observed that the increase in Mg content in HA P elevates the microhardness [11]. Salam and his group noticed that the increase in Mg content in HA P increases the electrical conduction and hence bioactivity of HA P increases [12]. Even though some of the researchers have studied the Zinc and Magnesium doped HA P they used a bulk amount of dopant.…”
Section: Introductionmentioning
confidence: 99%
“…Although it has a significant role in bone replacement and substitution, as it forms about 60-70% of human bones [4], its application is limited due to its low brittleness [5,6]. Therefore, several efforts were carried out in order to obtain similar biomaterials which can be used in such a role with a comparably higher order of stiffness with biocompatibility and biodegradability [3,7]. HA was doped and prepared artificially with several substances such as aluminum, iron, magnesium, zinc, strontium and sodium in order to improve its mechanical and electrical properties.…”
Section: Introductionmentioning
confidence: 99%